Keputusan Konsumen Menggunakan Maskapai Penerbangan di Indonesia - Tatiana, Yana; Sihombing, Theresia Glory Sarce; Adi, Erman Noor; Majid, Suharto Abdul; Ichwan, Gema Akbar (Institut Transportasi dan Logistik Trisakti, 2024)
The main problem of the research is the lack of security system and the low level of trust that could affect the decision to use an airline. The purpose of the study is to analyze the security, safety and trust variables directly on passengers’ decision to use Garuda Indonesia airline. This study used a multiple linear regression approach with validity, reliability, t-test, F-test and hypothesis testing. The research sample was 80 respondents taken from Garuda Indonesia flight service users in Soekarno-Hatta International Airport. The key findings of this study are the safety and trust variables directly have a positive effect on the passengers’ decision, while the safety variable does not have a positive effect on the passengers’ decision to use Garuda Indonesia airline.